2014
DOI: 10.1016/j.energy.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Life performance of oil and gas platforms: Site integration and thermodynamic evaluation

Abstract: Oil and gas platforms are energy-intensive systems, which operate under changing boundary conditions over time. In this paper, the life performance of an offshore platform is analysed by comparing three representative stages of an oil field (early-life, plateau and end-life productions). The energy requirements are assessed by a process integration study, and the system inefficiencies are pinpointed by performing an exergy accounting. The heating and cooling requirements vary significantly over time, and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…They found that the greatest exergy destruction take place in the gas treatment module. Nguyen et al [8] performed a study to assess the life efficiency of systems in an offshore platform using pinch-and exergybased methods. In this paper, they calculated the distribution of system and component exergy destruction at three life stages of the production.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the greatest exergy destruction take place in the gas treatment module. Nguyen et al [8] performed a study to assess the life efficiency of systems in an offshore platform using pinch-and exergybased methods. In this paper, they calculated the distribution of system and component exergy destruction at three life stages of the production.…”
Section: Introductionmentioning
confidence: 99%
“…Russia is the largest exporter of oil and gas, increasing the efficiency of the refinery is an urgent task requiring a thorough scientific approach to their study [1,2]. An oil refinery is a complex heat and power facility in which there are processes of heat generation and its use in production.…”
Section: Introductionmentioning
confidence: 99%
“…De Oliveira & Van Hombeeck [5] studied exergetic efficiency and losses of a Brazilian offshore platform. Nguyen et al [6] pinpointed exergy losses of an offshore platform for three stages of an oil field, while an exergy accounting was performed for six cases corresponding to different reservoir fluid compositions by Nguyen et al [7]. Voldsund et al [8] identified exergy losses of four platforms located in the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Voldsund et al [9] applied exergy analysis on a real production day of an offshore platform. Most of the studies [4,[6][7][8] stressed the importance of good use of the waste heat contained in the exhaust gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation